Primary Intestinal Lymphangiectasia and its Association With Generalized Lymphatic Anomaly - Victoria María Díaz Marugán; Juan Carlos Lopez-Gutierrez (Mazandaran University of Medical Sciences, 2016)
Background: Lymph is a fluid originating in the interstitial spaces of the body that contains cells, proteins, particles, chylomicrons, and sometimes bacteria. Objectives: The aim of the present study is to demonstrate that primary intestinal lymphangiectasia (PIL) results from a disruption of lymphatic circulation, thus corresponding to a secondary rather than a primary event in the context of generalized lymphatic anomaly. Materials and Methods: In this case series and record review, an analysis of intestinal lymphatic involvement was performed on patients diagnosed with PIL between 1965 and 2013. Of the 21 patients included in the study, 10 had been diagnosed before 5 years of age (1 prenatal), 8 between 5 and 18 years of age, and 3 while older than 18 years of age. The follow-up period varied between 1 and 34 years. Clinical data, blood and fecal parameters, imaging studies, endoscopy results, biopsy analyses, treatment details, and outcome information were collected from medical records. Endoscopy, histological studies, magnetic resonance imaging, and lymphoscintigraphy were performed on all patients. Dynamic intranodal lymphangiography was performed on 8 patients. Results: Central lymphatic channel obstruction was identified in 12 patients (57%). Associated lymphatic malformation (LM) was present in 16, diarrhea in 10, chylothorax in 11, chylous ascites in 10, pericardial effusion in 6, coagulopathy in 3, and osteolysis in 7. Conclusions: We consider intestinal lymphangiectasia not as an entity in itself, but as a consequence of lymphatic flow impairment in the thoracic duct, producing chylous reflux into the intestinal lymphatics.